Distribution of the newly invasive New Guinea flatworm Platydemus manokwari (Platyhelminthes: Geoplanidae) in Thailand and its potential role as a paratenic host carrying Angiostrongylus malaysiensis larvae. Issue 6 (20th September 2018) - Chaisiri, K.; Dusitsittipon, S.; Panitvong, N.; Ketboonlue, T.; Nuamtanong, S.; Thaenkham, U.; Morand, S.; Dekumyoy, P.
Abstract: Invasive species constitute one of the most serious threats to biodiversity and ecosystems, and they potentially cause economic problems and impact human health. The globally invasive New Guinea flatworm, Platydemus manokwari (Platyhelminthes: Geoplanidae), has been identified as a threat to terrestrial biodiversity, particularly soil-dwelling native species (e.g. molluscs, annelids and other land planarians), and is listed among 100 of the world's worst invasive alien species. We report here, for the first time, P. manokwari occurrences in many locations throughout Thailand, using voluntary digital public participation from the social network portals associated with the Thailand Biodiversity Conservation Group and collections of living flatworm specimens. Mitochondrial cytochrome c oxidase subunit I (COI) sequences confirmed that all collected flatworms were P. manokwari and placed them in the "world haplotype" clade alongside other previously reported specimens from France, Florida (USA), Puerto Rico, Singapore, French Polynesia, New Caledonia, and the Solomon Islands. In addition, infective stage larvae (L3) of the nematode Angiostrongylus malaysiensis were found in the flatworm specimens, with a 12.4% infection rate (15/121 specimens examined). Platydemus manokwari occurrence in Thailand and its capacity to carry L3 of Angiostrongylus should be of concern to biodiversity conservation and human health practitioners, because this invasive flatworm species may be involved in the life cycle of angiostrongylid worms in Thailand.